Are publicly held firms less efficient? Evidence from the US property-liability insurance industry - Xie, Xiaoying (Journal of Banking & Finance, 2010)
This paper studies the performance of publicly held firms in the US property-liability insurance industry by analyzing companies that issued initial public offerings (IPOs) from 1994 to 2005, using private firms as the benchmark. I investigate ex ante determinants and ex post effects of IPOs on firm efficiency, operating performance, and other financials. I also analyze stock returns and follow-on SEO and acquisition activities to provide further information on IPO motivation. The paper finds that the likelihood of an IPO significantly increases with firm size and premium growth. IPO firms experience no post-issue underperformance in efficiency, operations, or stock returns; register improvement in allocative and cost efficiency; and reduce financial leverage and reinsurance usage. Moreover, IPO firms are active in follow-on SEO issues and acquisition activities. The findings are mostly consistent with the theory that firms go public for easier access to capital and to ease capital constraints.